Emergence of Leptin in Infection and Immunity: Scope and Challenges in Vaccines Formulation - Alti, Dayakar; Sambamurthy, Chandrasekaran; Kalangi, Suresh K. (Frontiers in Cellular and Infection Microbiology, 2018)
Deficiency of leptin (ob/ob) and/or desensitization of leptin signaling (db/db) and elevated expression of suppressor of cytokine signaling-3 (SOCS3) reported in obesity are also reported in a variety of pathologies including hypertriglyceridemia, insulin resistance and malnutrition as the risk factors in host defense system. Viral infections cause the elevated SOCS3 expression, which inhibits leptin signaling. It results in immunosuppression by T-regulatory cells (Tregs). The host immunity becomes incompetent to manage pathogens’ attack and invasion, which results in the accelerated infections and diminished vaccine-specific antibody response. Leptin was successfully used as mucosal vaccine adjuvant against Rhodococcus equi. Leptin induced the antibody response to Helicobacter pylori vaccination in mice. An integral leptin signaling in mucosal gut epithelial cells offered resistance against Clostridium difficile and Entameoba histolytica infections. We present in this review, the intervention of leptin in lethal diseases caused by microbial infections and propose the possible scope and challenges of leptin as an adjuvant tool in the development of effective vaccines.